Pengaruh Minat Belajar dan Lingkungan Sekolah Terhadap Hasil Belajar IPS Siswa Kelas IX di SMP Negeri 2 Sawan - Lestari, Ni Luh Diah Putri; Dharmayasa, I Putu Arya (Universitas Pendidikan Ganesha, 2024)
This research aims to determine (1) the influence of interest in learning on learning outcomes in the social studies subject of Class IX Students of SMP Negeri 2 Sawan, (2) the influence of the school environment on learning outcomes in the social studies subject of Class IX Students of SMP Negeri 2 Sawan, and (3) the influence of interest in learning and the school environment on learning outcomes in social studies subjects for Class IX Students of SMP Negeri 2 Sawan. The type of research used is causal-type quantitative research. The sampling technique used is a probability sampling technique with random sampling. The sample for this research was class IX students of SMP Negeri 2 Sawan, with a total sample of 157 students. The data collection method uses a questionnaire and is analyzed using multiple linear regression. Instrument testing was carried out using validity and reliability tests. The classical assumption tests used are the normality test, multicollinearity test, and heteroscedasticity test. The research results show that (1) there is a positive and significant influence of interest in learning on learning outcomes, partially with a significance value of <0.001 <0.05. (2) There is a positive and significant influence of the school environment on learning outcomes, partially with a significance value of <0.001 <0.05. (3) There is a positive and significant influence between interest in learning and the school environment on learning outcomes simultaneously with a significance value of <0.001 <0.05.